2017
DOI: 10.1016/j.janxdis.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and racial differences in sleep duration: Results from a national survey of adults with cardiovascular disease

Abstract: Although Blacks sleep between 37–75 minutes less per night than non-Hispanic Whites, research into what drives racial differences in sleep duration is limited. We examined the association of anxiety sensitivity, a cognitive vulnerability, and race (Blacks vs. White) with short sleep duration (<7 hours of sleep/night), and whether anxiety sensitivity mediated race differences in sleep duration in a nationally representative sample of adults with cardiovascular disease. Overall, 1289 adults (115 Black, 1174 Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For instance, one recent study found that race significantly moderated the association between AS and cannabis use, such that AS-physical concerns significantly predicted cannabis-related problems among black, but not white, individuals (Dean, Ecker, & Buckner, 2017). In another study, AS mediated the association between race and differences in sleep duration among individuals with cardiovascular disease, such that being black (vs. white) was indirectly associated with decreased sleep duration through high AS (Alc antara, Cosenzo, Fan, Doyle, & Shaffer, 2017). These studies point to the importance of considering sociodemographic variables in the model of AS-health associations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one recent study found that race significantly moderated the association between AS and cannabis use, such that AS-physical concerns significantly predicted cannabis-related problems among black, but not white, individuals (Dean, Ecker, & Buckner, 2017). In another study, AS mediated the association between race and differences in sleep duration among individuals with cardiovascular disease, such that being black (vs. white) was indirectly associated with decreased sleep duration through high AS (Alc antara, Cosenzo, Fan, Doyle, & Shaffer, 2017). These studies point to the importance of considering sociodemographic variables in the model of AS-health associations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one recent study found that race significantly moderated the association between AS and cannabis use, such that AS-physical concerns significantly predicted cannabis-related problems among black, but not white, individuals (Dean, Ecker, & Buckner, 2017). In another study, AS mediated the association between race and differences in sleep duration among individuals with cardiovascular disease, such that being black (vs. white) was indirectly associated with decreased sleep duration through high AS (Alc antara, Cosenzo, Fan, Doyle, & Shaffer, 2017). These studies point to the importance of considering sociodemographic variables in the model of AS-health associations.…”
Section: Discussionmentioning
confidence: 99%
“…As described in greater detail elsewhere [27], we conducted a national online survey of adults living in the United States. Inclusion criteria included adult age defined as 18 years of age or older, and self-reported doctor or health professional diagnosis of MI.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, the total ASI score represented the higher-order anxiety sensitivity factor. Total scores for each of the anxiety sensitivity subdimensions were also calculated and the internal consistency estimates are provided below [27]: the physical concerns (Cronbach's α =0.92), social concerns (Cronbach's α =0.73), and cognitive concerns subscales (Cronbach's α =0.87).…”
Section: Methodsmentioning
confidence: 99%